BUDAYA KERJA KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI BERPRESTASI TENAGA PENDIDIK DI SEKOLAH MENENGAH KEJURUAN NEGERI 2 BATANG HARI - Nadya Rahmadani; Zilawati; Fitri Nasution (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
This research is motivated by the existence of an educational institution that has implemented a work culture by forming a group, but the work culture has not run maximally due to the classic problems such as many educators who are still not disciplined in terms of time, limited school budget, and different motivations from educators in developing competence. Therefore, the work culture in improving achievement motivation will run if the principal and educators can complete tasks well, overcome problems immediately, and commit to the tasks given. This research is a qualitative descriptive study from an educational perspective with data collection using observation, interview, and documentation methods. Then, data analysis is carried out using data reduction, data presentation, and conclusion drawing. The results of the research show that the principal's work culture in improving educators' achievement motivation has been well-implemented, including the principal always motivating educators to apply time discipline, the principal as a role model who is responsible for school policies, and encouraging teachers to develop their abilities through various educational activities. However, the obstacles in the work culture in improving educators' achievement motivation are the lack of discipline in terms of time, limited school budget policies, and different motivations from educators in developing competence. The solution to overcome the obstacles in the principal's work culture in improving educators' achievement motivation is for the principal to increase educators' discipline, submit requests for assistance to the education department, and continue to try to increase achievement motivation through developing educators' competence.